HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF TERHADAP KEJADIAN STUNTING PADA BALITA USIA 0 – 59 BULAN DI WILAYAH KERJA PUSKESMAS MONTA - Nurhidayah; Aris Iwansyah; Darmin; Muammar Iksan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Stunting is a chronic nutritional problem that remains a major public health concern in Indonesia because it can impair children's physical growth and cognitive development. One factor that is believed to be associated with stunting is a history of exclusive breastfeeding. This study aimed to determine the relationship between a history of exclusive breastfeeding and the incidence of stunting among children aged 0–59 months in the working area of Monta Community Health Center. This study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 96 mothers with children aged 0–59 months, selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-square test at a 95% confidence level (α = 0.05). A total of 83 respondents (86.5%) practiced exclusive breastfeeding, while 13 respondents (13.5%) did not. The Chi-square test showed a p-value of 0.851 (p > 0.05), indicating no statistically significant relationship between a history of exclusive breastfeeding and the incidence of stunting. The Odds Ratio (OR) of 1.119 (95% CI = 0.346–3.619) also indicated that exclusive breastfeeding was not a significant risk factor for stunting. In conclusion, a history of exclusive breastfeeding was not significantly associated with stunting among children aged 0–59 months in the working area of Monta Community Health Center. Nevertheless, exclusive breastfeeding should continue to be promoted as part of efforts to improve infant health, alongside adequate balanced nutrition and appropriate complementary feeding (MP-ASI).